Digitalized and harmonized industrial production systems : the PERoFORM approach - Colombo, Armando W. (Boca Raton, FL : CRC Press/Taylor & Francis, 2019)
"After a Technology Trend Screening and beyond a comprehensive State-of-the-Art analysis about Industrial Digitalization and Industry 4.0-compliant solutions, the book introduces methods, architectures, and technologies applicable in real industrial use cases, explained for a broad audience of researchers, practitioners and industrialists"--
OCLC-licensed vendor bibliographic record.
Keywords: Flexible manufacturing systems; Manufacturing processes -- Automation; COMPUTERS / Operating Systems / General; COMPUTERS / Computer Engineering; TECHNOLOGY / Electricity